THE COOKING INFLUENCE ON THE CHARACTERISTICS OF COMPOTES BASED ON PRICKLY PEAR AND DATE SYRUPS - ASMA TEMAGOULT; BARIZA ZITOUNI; YASSINE NOUI; BOUTHEYNA SI BELKHIR; FATMA Z. BENSADI (Scientific Study & Research: Chemistry & Chemical Engineering, Biotechnology, Food Industry)
The Mech-Degla and Frezza dates (sorting gaps of the Deglet-Nour date) are Algeria's most common varieties of dates (Phoenix dactylifera L.). These dry dates are rich in sugars and can be transformed into various food products like syrup, which is used as a natural sweetener. This work aims to study the influence of cooking on the physicochemical properties of compote prepared from prickly pear and date syrup, compared to control compote. The date syrup is characterized by a high content of sugars (61.90 - 64.70 %), total acidity (0.20 - 0.21 %), ash (3.90 - 3.91 %), and total polyphenols (17.17 - 17.24 %). The prickly pear is a very water-rich fruit with a content of 84 % and a total soluble solids content of 14.5 %. Three formulas of compotes are elaborated on the prickly pear sweetened with two date syrups (Mech-Degla and Freeza) and with sucrose (control). Also, a strong impact of cooking on the compote’s physicochemical properties was established, especially, on the polyphenol contents that decrease after cooking, in addition to the titratable acidity, and the pH. The DPPH decrease to 52 - 68 % compared to the fruit and syrups DPPH (62.5 – 80.66 %).